'Solitary idiopathic choroiditis' or a tumour of scleral origin: A case report based hypothesis. (June 2020) - Kumar, Prashant; Chawla, Rohan; Balakrishnan, Jyothi; Kumar, Atul; Kumar, Atin
Abstract: We here hypothesize the scleral origin of 'Solitary Idiopathic Choroiditis', a yellowish, nodular lesion that resembles other choroidal tumors. Systemic investigations were done to rule out causes like tuberculosis and sarcoidosis. Multimodal imaging was done for better characterization and to distinguish it from other choroidal lesions. Fundus imaging revealed a yellowish-orange, well-defined nodular lesion resembling solitary idiopathic choroiditis inferotemporal to the disc. Swept source optical coherence tomography (SSOCT) showed a nodular lesion arising from the sclera with compression of overlying choroid. Indocyanine green angiography (ICGA) showed hypofluorescence in all phases of angiogram with displacement of major choroidal vessels along the walls of the mass and loss of overlying choriocapillaries. The same was evident on Swept Source optical coherence tomography angiography (SSOCTA) as well. Fundus autofluorescence (FAF) showed central hypofluoresence with surrounding hyperfluorescence. Ultrasound (USG) B scan revealed a high reflective echo at the apex of the mass with moderate internal reflectivity without any evidence of calcification. Enhanced Infrared (IR) Reflectance imaging revealed a central intense hyerreflective area suggestive of a fibrotic mass. Magnetic reasonance imaging (MRI) revealed a focal hypointense nodular lesion on T2-weighted image. The central white area at the apex with corresponding hypoautofluorescence, a high spike on ultrasound, intense hyperreflectivity on enhanced Infrared reflectance, lack of vascularity and displacement of choroidal vessels is suggestive of a scleral origin of the mass and likely fibrotic nature.